Frozen cultural plasticity. (2016) - Houdek, Petr; Novakova, Julie
Abstract: We discuss cultural group selection under the view of the frozen plasticity theory and the different explanatory power and predictions of this framework. We present evidence that cultural adaptations and their influence on the degree of cooperation may be more complex than presented by Richerson et al., and conclude with the gene-environment-culture relationship and its impacts on cultural group selection.